A critical review of the Cabinet Circular on Te Tiriti o Waitangi and the Treaty of Waitangi advice to ministers - O’Sullivan, Dominic; Came, Heather; McCreanor, Tim; Kidd, Jacquie (Ethnicities, 2021)
The New Zealand state developed from a treaty between the British Crown and hapū (sub-tribes) in 1840. The te Reo (Māori language) text and the English version of the agreement are fundamentally different. Breaches of this treaty and tension over how the political relationship between Māori and the Crown should proceed are ongoing. In 2019, the Cabinet Office issued a Circular instructing bureaucratic advisers of the questions they should address when providing advice to ministers on the agreement’s contemporary application. In this article, we use Critical Tiriti Analysis (CTA) – an analytical framework applied to public policies – to suggest additional and alternative questions to inform bureaucratic advice. The article defines CTA in detail and shows how using it in this way could protect Māori rights to tino rangatiratanga (a sovereignty and authority that is not subservient to others) and substantive engagement, as citizens, in the formation of public policy. This article’s central argument is that the Circular reflects an important evolution in government policy thought. However, in showing how the Circular privileges the English version (the Treaty of Waitangi) over the Māori text (Te Tiriti o Waitangi), the article demonstrates how Māori political authority remains subservient to the Crown in ways that Te Tiriti did not intend. We show through the conceptual illustration of the care and protection of Māori children, despite the significant evolution in government thought that it represents, these rights are not fully protected by the Circular. This is significant because it was Te Tiriti, with its protection of extant Māori authority and sovereignty, that was signed by all but 39 of the more than 500 chiefs who agreed to the British Crown establishing government over their own people, but who did not agree to the colonial relationship which may be read into the English version.
Keywords: Cabinet; Critical Tiriti Analysis; Public Policy; Self-Determintation; Te Tiriti o Waitangi; Treaty of Waitangi

Critical Tiriti Analysis: A prospective policy making tool from Aotearoa New Zealand - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Tim (Ethnicities, 2023)
Restrictions on Indigenous peoples’ contributions to policymaking pervade post-settler societies like Australia, Canada and Aotearoa. Such effects are observed in spite of agreements like Te Tiriti o Waitangi in Aotearoa and the United Nations’ Declaration on the Rights of Indigenous Peoples. Te Tiriti, negotiated between the British Crown and Māori (Indigenous peoples of Aotearoa), may have been entered into honourably by both parties, but the Crown has consistently resisted its implementation. Contemporary colonialism is characterised by the entrenched and on-going displacement of Indigenous people’s authority by settler states, rationalised by race as a determinant of human worth. Impacts include land alienation, unsustainable resource exploitation and marginalising Indigenous voices from opportunities to make policy consistent with Indigenous values and preferred ways of living. Colonialism normalises institutional racism so that public policy outcomes are persistently unjust. This article describes Critical Tiriti Analysis (CTA), an original contribution to transforming colonial policy, which retrospectively evaluates whether any specific policy document is consistent with Te Tiriti. Substantial interest in CTA from policymakers, practitioners, and scholars led to the development of the tool as a prospective guide to making policy that is consistent with authoritative interpretations of Te Tiriti, and therefore, more likely effective in producing public policies which eliminate inequities. CTA was initially focused on health policy and built on a series of questions that arise from our interpretations of the text of Te Tiriti, contemporary Tiriti scholarship and jurisprudence, and our observations of the ways in which the method is being used by ourselves and others. Although deeply grounded in Aotearoa, we argue that CTA may be transferable to other colonial contexts, such as the Australian where treaties between First Nations and the state are being contemplated, and Canada which has passed legislation to implement the Declaration on the Rights of Indigenous Peoples.
Keywords: Public Policy; Te Tiriti o Waitangi